2,7‐Substituted N‐Carbazole Donors on Tris(2,4,6‐trichlorophenyl)methyl Radicals with High Quantum Yield - Chen, Lisa; Arnold, Mona; Kittel, Yonca; Blinder, Rémi; Jelezko, Fedor; Kuehne, Alexander J. C. (Advanced optical materials, 2022)
Doublet spin properties of organic open‐shell luminophores evade the formation of dark triplet states, thus making radicals favorable emitters for next generation organic light‐emitting diodes. However, their poor photostability and mediocre photoluminescence quantum yields (PLQYs) limit their application. In this work, two series of trityl radicals functionalized with one, two, and three 2,7‐disubstituted carbazole units are presented. The authors either attach nitriles or bromines as electron‐withdrawing 2,7‐substituents. The resulting radical emitters exhibit outstanding optical properties. The electron‐withdrawing properties of the substituents lead to a blue‐shift of the emission, indicating a starting point for future emission engineering into the green spectrum. Due to the 2,7‐substitution of the carbazole moiety, the radical emitters are sterically more hindered than the commonly used 3,6‐substituted carbazoles. This steric hindrance reduces non‐radiative decay pathways in the molecules, enhancing photostability and pushing PLQYs up to 87%. Quantum mechanical calculations elucidate the influence of the electron withdrawing substituents on the optical performance of the open‐shell molecules. The authors also show that intensity borrowing from higher lying locally excited states contributes to these exceptionally high PLQYs. Two series of trityl radicals functionalized with one to three 2,7‐disubstituted carbazole units are presented, carrying either nitriles or bromines as substituents. These electron‐withdrawing substituents in 2,7‐position induce a blue‐shift of emission and exceptional photoluminescence quantum yields up to 87%. Quantum mechanical calculations elucidate the electronic and steric properties of the molecules responsible for the outstanding optical performance.